Komodifikasi Perempuan dalam Tradisi Uang Panai' - A Mappatunru; Sriwiyata Ismail Zainuddin (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
This article departs from the view that the dynamics of traditional society are inseparable from upheavals and contradictions based on class and gender. This article aims to conduct an explanatory critique of the uang panai' tradition, which is generally viewed romantically as a tradition that upholds the dignity and honor of women. This article is qualitative research with a critical social science approach. Data was obtained through literature studies, observations, and interviews. This research reveals three things, (1) the current practice of uang panai' tradition tends to reflect gender inequality which is possibly caused by gender construction, that inherently rooted in the notion of siri', (2) Contrary to the romantic view, the practice of uang panai' tradition can be described as a phenomenon of the commodification of women that occurs in the matrimonial market where women experience layered symbolic burdens, and (3) gender construction in the notion of siri' brings women through marriage into the circuit of capital, then absorbs the value of their work as unpaid domestic labor to ensure the sustainability of capital in the capitalist mode of production. This article invites us to rethink the concept of family where women can be sovereign over themselves.